Long‐Term Demographic Trends of Near Threatened Coastal Dolphins Living in an Urban Estuary - Kennadie Haigh; Guido J. Parra; Luciana Möller; Aude Steiner; Mike Bossley (Ecology and Evolution)
ABSTRACT Understanding population demography of threatened species and how they vary in relation to natural and anthropogenic stressors is essential for effective conservation. We used a long‐term photographic capture‐recapture dataset (1993–2020) of Indo‐Pacific bottlenose dolphins (Tursiops aduncus) in the highly urbanised Adelaide Dolphin Sanctuary (ADS), South Australia, to estimate key demographic parameters and their variability over time. These parameters were analysed in relation to environmental variables used as indicators of local and large‐scale climatic events. Our findings indicate that apparent survival was high (0.98–0.99) and did not vary seasonally. Estimates of abundance were not directly related to environmental variables but were linked to seasonal temporary emigration. Abundance peaked in summer with an average of 85.37 dolphins (SD = 30.23) and was lowest in winter, with 68.57 (SD = 24.70) individuals. Site fidelity at the population level was low, but lagged identification rates revealed a population of approximately 28 individuals at any one time. Trend analysis suggests an increase in dolphin abundance from 1993 and persistence of the population over decades despite significant urbanisation, although numbers have declined in more recent years. Further research is needed to understand the cumulative impacts leading to this population decline and to assess its future viability under different management scenarios. Conservation strategies aimed at increasing reproductive rates and promoting connectivity to adjacent waters are likely to be more effective in reversing population declines.